A Validation Study of the Postpartum Bonding Questionnaire in Iranian Mothers - Abbas Ebadi; Fatemeh Ghavidel; Hamid Sharif Nia; Seyedeh Zahra aemmi (مراقبت پرستاری و مامایی ابن سینا)
Background and Objective: Postpartum bonding disorder is a significant impairment in the mother-infant relationship during the postpartum period. The present study aimed to translate and validate the Postpartum Bonding Questionnaire (PBQ) in Iranian mothers. Materials and Methods: A descriptive, cross-sectional survey design was employed in the current investigation. With the developer's permission, a back-translation procedure was used to translate the original questionnaire from English to Persian. Then, following qualitative face validity, a sample of primiparous mothers completed the questionnaire, and construct validity was assessed using exploratory factor analyses. Moreover, reliability was evaluated using internal consistency analysis (average inter-item correlation, Cronbach’s alpha, and McDonald’s omega) and construct reliability. Results: A total of 263 primiparous mothers completed the questionnaire. Exploratory factor analysis revealed the 13-item version of the PBQ with a three-factor (‘general factor,’ ‘rejection and anger,’ and ‘anxiety about care’) structure, which explained 49.19% of the overall variance observed, and this confirmed the construct validity of the tool. Cronbach's alpha coefficient for the subscales was equal to 0.744. In addition, the test-retest reliability (0.850-0.952) of the questionnaire with a two-week interval indicated an acceptable range of reliability. Conclusion: The findings indicate that the Persian version of the 25-item PBQ is a reliable and valid tool for screening and identifying the postpartum bonding disorder among Iranian mothers.